Um CRIS para uma Unidade de Investigação - Daniel Moreira Couceiro (2017)
This project is inserted in the Research Units (UI) context, whereas the main case study is Instituto de Engenharia de Sistemas e Computadores, Tecnologia e Ciência (INESC TEC). This type of organizations requires a careful management of its information and resources. Typically, the individuals work in projects, which may envolve external entities, such as financiers, partners or addressees. These projects produce several types of results which include reports, prototypes, data sets, publications or patents. All of this information is used internally, for the evaluation of the individuals and the various organic structures which compose the organization, and externally, for the divulgation of results and its activity. The information system that contemplates these entities and the relations among them is commonly known as Current Research Information System (CRIS) and has been target of normalization. One of the standards, proposed by the European Union, and developed and maintained by euroCRIS is named Common European Research Information Format (CERIF). This standard formalizes the research related entities and its relations, thus emphasizing the interoperability among different systems. With this project, it is expected to design a CRIS and contribute to an implementation in INESC TEC, while having in mind the formalized orientations in CERIF and the existing information systems. This system should include the management of research projects, its teams, milestones and results. Furthermore, it should relate the projects with the involved researchers, publications and research data repositories and comprise the production of metrics along internal and external perspectives.